Zatorska goose - a subject of parasitological research - Kornaś, Sławomir; Basiaga, Marta; Kowal, Jerzy; Nosal, Paweł; Wierzbowska, Izabela; Kapkowska, Ewa (Annals of parasitology, 2015)
The aim of the study was to determine the level of gastrointestinal parasites in a native breed of geese - Zatorska goose - based on coproscopic testing. Faecal samples were collected from 90 young geese in three age groups (5, 7 and 9 weeks old) in 2014. The geese were kept indoors on deep litter and pastured from spring to autumn. The area of the pastures around the buildings where the geese grazed was about 1 hectare, divided into quarters for different age groups. Before grazing, the birds were dewormed with fenbendazole (Fenbenat powder 4%, Naturan). As additional treatment for coccidiosis, coccidiostats were added to the feed. The study was conducted using the McMaster quantitative method with centrifugation (flotation liquid: NaCl and glucose). The birds were shown to be infected with coccidia and nematodes. The prevalence of Eimeria sp. infection (mean 40%) and the number of oocysts per gram of faeces (reaching 5,300 OPG) were highest in the youngest age group of geese. The level of Amidostomum anseris infection was similar in the three age groups, with prevalence from 40% to 50% (nematode egg output ranged from 50 to 350 eggs per gram of faeces, EPG). Capillaria anatis was observed only in 5- and 7-week-old geese.